Water pollution challenges and future direction for water resource management policies in Malaysia - Rafia, Afroz; Mehedi Masud, Muhammad; Akhtar, Rulia; Duasa, Jarita (Sage Publications, 2014)
Water pollution is a major problem in the global environment. This necessitates continuing assessment and review of water resource policy at all levels. The main objectives of this article are to investigate major sources of water pollution, water resource policies and challenges to improve water quality in Malaysia. The findings indicate that the major problem associated with water pollution is that human heart and kidneys can be adversely affected if polluted water is consumed regularly. Other health problems associated with polluted water are poor blood circulation, skin lesions, vomiting, cholera, gastroenteritis and damage to the nervous system. It also highlighted that residential, agricultural and industrial wastes are three main sources of river pollution in Malaysia. This article also identified several challenges fronting as rural water supply and sanitation, recreational water and safe drinking water in Malaysia. Finally, we discuss the water resource policies in Malaysia and provide some recommendations that will be helpful for policymakers to improve river water quality, particularly in Malaysia.